The flipped english language learning through microsoft team application: analytical post covid-19 pandemic critical study - Rizky Eka Prasetya (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
The increasing influence of flipped learning within these approaches has brought significant changes to transformational approaches that solve several challenges in conventional curriculum programs. The research aimed to look at how students felt about using a flipped learning paradigm in two classes teaching English as a foreign language and determine whether it was technically feasible. The Flipped Learning Experience Questionnaire results result from the Flipped Learning Experience Questionnaire were evaluated using the Wilcoxon signed ordered test. In a flipped approach, 84 participants used their Microsoft Team platform to study English as a Foreign Language class. The findings revealed that the flipped instructional material was perceived positively, especially regarding overall pleasure. The learning attitudes mean score in the flipped arrangement was significantly greater than in the traditional design, increasing throughout the study. The results suggest that participants acknowledged the ease of use of Microsoft Teams platform devices and emphasized the significance of a good video content design for successful flipped educational experiences through Microsoft Teams. Further investigation is needed since students encountered difficulties throughout the assignment